Enhancing the Conceptual Comprehension on Photosynthesis by Implementing Outdoor Study for Grade 4 Students of SDN Bratan I In Academic Year 2014/2015 - Rintayati, Peduk (Proceeding of International Conference on Teacher Training and Education, 2016)
The objective of this research is to improve the conceptual comprehension on photosynthesis by implementing Outdoor Study. This research is a Classroom Action Research (CAR) conducted in two cycles. Every cycle consisted of four steps namely planning, action, observation, and reflection. Teachers and fourth grade students were the subject and sources of data in this research. The techniques of collecting data in this research were documentation, interview, observation, and test. The methods of data validity used were triangulation of source and triangulation of technique. The techniques of data analysis used in this research were comparative descriptive and interactive technique analysis. Conclusion of this research is implementing Outdoor Study can enhance the conceptual comprehension on photosynthesis.Â